Azolla Cultivation benefits rural women in Cooch Behar - Biswas, Soma; Mitra, Biplab (Indian Farming, 2016)
In Cooch Behar district of West Bengal, livestock plays an important role in village economy. Feeding the cattle throughout the year with commercial feed is a great problem for resource poor villagers. However, inclusion of Azolla in regular feed items could decrease the feed cost on one hand and on other hand could increase the milk yield of milch cattle. With the concentrated effort of Krishi Vigyan Kendra, there is a growing popularity of Azolla cultivation in Cooch Behar district among the rural women.